Relative exposure index: An important factor in sea turtle nesting distribution - Santana Garcon, Julia; Grech, A.; Moloney, J.; Hamann, M. (2010)
1. The threatened status of many sea turtle populations and their vulnerability to coastal development and predicted climate change emphasize the importance of understanding the role of environmental factors in their distribution and ecological processes. The factors driving the distribution of sea turtle nesting sites at a broad spatial scale is poorly understood. 2. In light of the lack of understanding about physical factors that drive the distribution of turtle nesting, the relationship between nesting site distribution and the exposure of coastal areas to wind and wind-generated waves was analysed. To achieve this, a Relative Exposure Index (REI) was developed for an extensive area in northeastern Australia and values of the index for nesting sites of five different sea turtle species and randomly selected non-nesting sites were compared. 3. Although there are differences between species, the results show that sea turtles nest in areas of higher REI values suggesting that wind exposure is related to the spatial distribution of sea turtle nesting sites, and it may also influence nest site selection in female turtles and/or the dispersal of hatchlings towards oceanic currents. 4. The combination of these results with further research on other driving environmental factors, like oceanic currents, has the potential to allow for the identification and prediction of future nesting sites, for which conservation and management may become essential. © 2009 John Wiley & Sons, Ltd.